CUSTOMER RELATIONSHIP MANAGEMENT DAN CUSTOMER VALUE PENGARUHNYA TERHADAP KEPUASAN NASABAH SERTA IMPLIKASINYA TERHADAP LOYALITAS NASABAH PADA NASABAH KREDIT KOMERSIL PT. BANK SULUTGO KANTOR CABANG UTAMA MANADO - Rompas, Jeifer J. L.; Mananeke, Lisbeth; Worang, Frederik G. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Customer Relationship Management and Customer Value influence on Customer Satisfaction and the effect on the loyalty of commercial credit customers at PT. Bank SulutGo, Manado Main Branch Office. This study aims to 1) Analyze the influence of Customer Relationship Management on commercial credit customer satisfaction. 2) Analyzing the effect of Customer Value on customer satisfaction of commercial credit. 3) Analyzing the effect of Customer Relationship Management on the loyalty of commercial credit customers. 4) Analyzing the effect of Customer Value on the loyalty of commercial credit customers. 5) Analyzing the effect of satisfaction on the loyalty of commercial credit customers. This research is a quantitative study which adopts path analysis model. The data used are primary and were obtained using a questionnaire. Data was collected from 100 samples that are commercial credit customers of PT. Bank SulutGo, Manado Main Branch Office. The research findings conclude that 1) Customer Relationship Management has a significant influence on Customer Satisfaction of commercial credit. 2) Customer Value has a significant influence on Customer Satisfaction of commercial credit. 3) Customer Relationship Management has a significant direct effect on customer loyalty for commercial credit. 4) Customer Value has a significant direct effect on the loyalty of commercial credit customers. 5) Satisfaction has a significant influence on Customer Loyalty, as well as mediating Customer Relationship Management and Customer Value variables to Customer Loyalty variablesÂ Keywords: Â customer relationship management, customer value, customer satisfaction, customer loyaltyÂ